2019
DOI: 10.1105/tpc.19.00179
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Availability Regulates TORC1 Signaling via LST8 in Chlamydomonas

Abstract: Target of rapamycin complex 1 (TORC1) is a central regulator of cell growth. It balances anabolic and catabolic processes in response to nutrients, growth factors, and energy availability. Nitrogen-and carbon-containing metabolites have been shown to activate TORC1 in yeast, animals, and plants. Here, we show that phosphorus (P) regulates TORC1 signaling in the model green alga Chlamydomonas (Chlamydomonas reinhardtii) via LST8, a conserved TORC1 subunit that interacts with the kinase domain of TOR. P starvati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 60 publications
(125 reference statements)
6
51
0
Order By: Relevance
“…The LST8 subunit of TOR is down-regulated under P-starvation in a PSR1 -dependent fashion. This pathway appears to link P-stress to TOR-mediated de-repression of TAG synthesis and autophagy, along with repression of translation ( Couso et al, 2020 ). Investigation of the signal transduction pathway in S deprivation in Chlamydomonas has clearly identified SNRK-family involvement ( Gonzalez-Ballester et al, 2008 ; González-Ballester et al, 2010 ) but this kinase group have also been implicated more widely in other stress responses in this alga ( Colina et al, 2019 ) ( Figure 6 ).…”
Section: Regulation Of Phosphate Metabolism In Microalgaementioning
confidence: 99%
See 1 more Smart Citation
“…The LST8 subunit of TOR is down-regulated under P-starvation in a PSR1 -dependent fashion. This pathway appears to link P-stress to TOR-mediated de-repression of TAG synthesis and autophagy, along with repression of translation ( Couso et al, 2020 ). Investigation of the signal transduction pathway in S deprivation in Chlamydomonas has clearly identified SNRK-family involvement ( Gonzalez-Ballester et al, 2008 ; González-Ballester et al, 2010 ) but this kinase group have also been implicated more widely in other stress responses in this alga ( Colina et al, 2019 ) ( Figure 6 ).…”
Section: Regulation Of Phosphate Metabolism In Microalgaementioning
confidence: 99%
“…Functional gene categories are indicated to the left. The information and models shown are a collation of transcriptomic data and molecular work from published sources: ( Moseley et al, 2006 ; Gonzalez-Ballester et al, 2008 ; González-Ballester et al, 2010 ; Toepel et al, 2011 ; Schmollinger et al, 2014 ; Bajhaiya et al, 2016 ; Wild et al, 2016 ; Couso et al, 2018 ; Couso et al, 2020 ).…”
Section: Regulation Of Phosphate Metabolism In Microalgaementioning
confidence: 99%
“…In addition, these reports indicate an interaction between TOR signaling network and lipid metabolism in algae (Pérez-Pérez et al, 2017). Most recently, through the characterization of a hypomorphic mutant of the LST8 gene, lst8-1 under P deficiency, Couso et al (2020) demonstrated that P deficiency reduces the abundance of LST8 proteins and downregulates activity of TORC1 to activate autophagy and TAG synthesis in Chlamydomonas (Figure 1). In the N-deficient conditions, any significant phenotype was not observed in the lst8-1 mutant.…”
Section: Algal Autophagy In Tor Signalingmentioning
confidence: 93%
“…The mechanisms of GCN2 perception in plants are unknown, although GCN2 activation by uncharged tRNAs appears to be universal in eukaryotes (Li et al, 2013) (Figure 1A). Prolonged carbon starvation (Huang et al, 2019) and phosphate deficit which causes ER stress (Naumann et al, 2019) induce autophagy independently of TOR, although recent research in Chlamydomonas suggests LST8, the stabilizer of TOR, is involved in phosphate starvation response (Couso et al, 2020).…”
Section: Tor Kinase As a Central Modulator Of Atg Proteinsmentioning
confidence: 99%